Pneumonia Disease detection using the convolutional neural network - Ashrafee, Md. Iftid; Sourav, Koushik Barmon; Dolna, Mahazabin Khan; Haque, Samia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.